Small-Scale Geochemical Heterogeneities and Seasonal Variation of Iron and Sulfide in Salt Marshes Revealed by Two-Dimensional Sensors - Zhu, Qingzhi; Cochran, J. Kirk; Heilbrun, Christina; Yin, Hang; Feng, Huan; Tamborski, Joseph J.; Fitzgerald, Patrick; Cong, Wen (Frontiers in Earth Science, 2021)
Loss of tidal wetlands is a world-wide phenomenon. Many factors may contribute to such loss, but among them are geochemical stressors such as exposure of the marsh plants to elevated levels on hydrogen sulfide in the pore water of the marsh peat. Here we report the results of a study of the geochemistry of iron and sulfide at different seasons in unrestored (JoCo) and partially restored (Big Egg) salt marshes in Jamaica Bay, a highly urbanized estuary in New York City where the loss of salt marsh area has accelerated in recent years. The spatial and temporal 2-dimensional distribution patterns of dissolved Fe2+ and H2S in salt marshes were in-situ mapped with high resolution planar sensors for the first time. The vertical profiles of Fe2+ and hydrogen sulfide, as well as related solutes and redox potentials in marsh were also evaluated by sampling the pore water at discrete depths. Sediment cores were collected at various seasons and the solid phase Fe, S, N, C and chromium reducible sulfide in marsh peat at discrete depths were further investigated in order to study Fe and S cycles, and their relationship to the organic matter cycling at different seasons. Our results revealed that the redox sensitive elements Fe2+ and S2- showed significantly heterogeneous and complex three dimensional distribution patterns in salt marsh, over mm to cm scales, directly associated with the plant roots due to the redox diagenetic reactions. The overall concentrations of Fe2+ and H2S and distribution patterns also seasonally varied with temperature change. H2S level in JoCo sampling site could change from <0.02 mM in spring to >5 mM in fall season, reflecting significantly seasonal variation in the rates of bacterial oxidation of organic matter at this marsh site. Solid phase Fe and S showed that very high fractions of the diagenetically reactive iron at JoCo and Big Egg were associated with pyrite that can persist for long periods in anoxic sediments. This implies that there is insufficient diagenetically reactive iron to buffer the pore water hydrogen sulfide through formation of iron sulfides at JoCo and Big Egg.